2002
DOI: 10.1074/jbc.m206366200
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Architecture of Plant Cells

Abstract: The changes in the intermediary metabolism of plant cells were quantified according to growth conditions at three different stages of the growth cycle of tomato cell suspension. Eighteen fluxes of central metabolism were calculated from 13 C enrichments after near steady-state labeling by a metabolic model similar to that described in Dieuaide-Noubhani et al. (Dieuaide-Noubhani, M., Raffard, G., Canioni, P., Pradet, A., and Raymond, P. (1995) J. Biol. Chem. 270, 13147-13159), and 10 net fluxes were obtained di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(59 citation statements)
references
References 44 publications
4
54
0
1
Order By: Relevance
“…These estimates of carbon use efficiency are within the range obtained for other heterotrophic plant systems, including a rosy periwinkle hairy root culture (24%; Sriram et al, 2007), maize root tips (42%-47%; Alonso et al, 2007b), developing sunflower embryos (50%; Alonso et al, 2007a), and a tomato cell culture (52%-68%; Rontein et al, 2002). Although considerably higher values have been reported for developing embryos of oilseed rape (85%-95%) and soybean (82%-83%), in these systems there is appreciable reassimilation of respired CO 2 through Rubisco, and light makes significant contributions to the provision of ATP and/or reductant required for biosynthesis (Goffman et al, 2005;Allen et al, 2009).…”
Section: Energy and Redox Balance In Plant Metabolic Networkmentioning
confidence: 55%
See 1 more Smart Citation
“…These estimates of carbon use efficiency are within the range obtained for other heterotrophic plant systems, including a rosy periwinkle hairy root culture (24%; Sriram et al, 2007), maize root tips (42%-47%; Alonso et al, 2007b), developing sunflower embryos (50%; Alonso et al, 2007a), and a tomato cell culture (52%-68%; Rontein et al, 2002). Although considerably higher values have been reported for developing embryos of oilseed rape (85%-95%) and soybean (82%-83%), in these systems there is appreciable reassimilation of respired CO 2 through Rubisco, and light makes significant contributions to the provision of ATP and/or reductant required for biosynthesis (Goffman et al, 2005;Allen et al, 2009).…”
Section: Energy and Redox Balance In Plant Metabolic Networkmentioning
confidence: 55%
“…The bottom row contains an analysis of data combined from all three feeding strategies (1/2/U-13 C), in which the SD of all isotopomer measurements was reduced to 5%. a single plastidic pathway has been assumed in maize root tips (Dieuaide-Noubhani et al, 1995;Alonso et al, 2007b), tomato (Solanum lycopersicum) cell cultures (Rontein et al, 2002), and Arabidopsis cell cultures (Williams et al, 2008), whereas complete duplication of the pathway in the cytosol and plastid has been assumed in the analysis of cultured soybean embryos (Sriram et al, 2004;Iyer et al, 2008). In some tissues, such as oilseed rape embryos (Schwender et al, 2003) and soybean embryos (Allen et al, 2009), the modeling task is made easier because the observed labeling patterns imply that intermediates in glycolysis and the PPP are in fast exchange between the cytosol and the plastids, ensuring that duplicate pathways in different physical locations function indistinguishably from a single uncompartmented pathway.…”
Section: Quantifying the Compartmented Fluxes Of Central Metabolismmentioning
confidence: 99%
“…These characteristics represent a mechanism of allosteric regulation of enzymes of central metabolic pathways (40). The presence of three different NAD-MEs originating by alternative associations of NAD-ME1 and -2 may be a novel phenomenon unique to plant mitochondria.…”
Section: Is the Formation Of Alternative Oligomeric Forms A Fine-tunimentioning
confidence: 99%
“…A number of different possible metabolic roles of HXKs have been recently described (Claeyssen and Rivoal 2007). Mitochondrial HXKs are thought to have preferred access to ATP produced in respiration for consumption by active metabolite fluxes through sucrose cycling, glycolysis, and sugar nucleotide syntheses (Rontein et al 2002;Graham et al 2007). …”
Section: Introductionmentioning
confidence: 99%